OVERCOMING FRICATIVE BARRIERS: UNDERSTANDING ENGLISH FRICATIVES IN KUWAITI ARABIC LEARNERS - Al-Ardhiya, Sarah Khalid; Al-Ardhiya, Ahmed Youssef (Top Linguistic and Language Journal (TLLJ), 2023)
This paper aims to investigate the perception of English labial [v] and post-alveolar [ʒ] fricatives by undergraduate students in Kuwait, who speak Kuwaiti Arabic as their native language and are studying English. The study administered perception tests including the identification and discrimination tests for phonetic and lexical phonological perception. The data obtained from 104 female native speakers of Kuwaiti Arabic studying in the College of Basic Education in Kuwait were analysed using reliable and consistent techniques. The results show that the perception of English [v] was better than [ʒ] on all word positions. Moreover, the students’ perception of [ʒ] showed difficulty in different word positions. The study also provides an analysis of models for second language acquisition, including Flege’s Speech Learning Model (SLM), Brown’s Feature Model (FM) and Best’s Perceptual Assimilation Model (PAM), and their relevance to the perception difficulties of undergraduate students of English from Kuwait. The study highlights the importance of understanding the perception-related issues of second-language acquisition and its potential challenges for Arabic learners in learning English fricatives.